Treatment of Infected Nonunion of Fracture of the Proximal Third of Tibia Using Ilizarov Ring Fixator: A Case Series - Madhura Sujay Kulkarni; Milind Kulkarni; Ruta Kulkarni (Journal of Limb Lengthening & Reconstruction)
Introduction: Nonunions (NUs) of the fractured proximal third of the tibia are challenging to manage owing to a capacious canal and scarce anterior soft-tissue cover. Infection further complicates the use of internal fixators in such patients. We present a study of 25 cases of infected NU of the proximal third of the tibia that we treated using the Ilizarov ring fixator over 10 years. Materials and Methods: Twenty-three men and two women with infected NU of the proximal tibial meta-diaphyseal junction were studied. The mean age of the patients was 39.2 years. Treatment involved thorough debridement of the NU site with freshening of the bone ends followed by the application of a 3-ring hybrid Ilizarov construct. The patients were followed at regular intervals to assess the infection control, union, limb function, and complications. Results: Successful union and eradication of infection were achieved in 21 patients. Union was not satisfactory in four cases. The average fixator time was 7.12 months. Average knee flexion of 99.2° was observed. The Association for the Study and Application of the Methods of Ilizarov score was excellent in 56% of cases and good in 28%. Six patients required soft-tissue reconstruction. One patient suffered a fracture at the distal pin site while one had a refracture 4 months after treatment completion. Three patients developed a discharging sinus which required debridement and oral antibiotics. Conclusion: The Ilizarov construct provides multilevel, multidirectional, and multiplanar stability, aiding early mobility. Appropriate case selection, sound soft-tissue reconstruction, robust infection control, and good patient compliance are important for the success of the treatment.